LAW ENFORCEMENT AGAINST THE POLICE PROFESSIONAL CODE OF ETHICS DUE TO DESERTION COMMITTED BY POLICE MEMBERS ENDING IN DISHONORABLE DISCHARGE - Putra, Alghoni Bumantara; Kadaryanto, Bagio; Pardede, Rudi (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The police disciplinary code reflects a noble ideal and aspiration—namely, to uphold and maintain the image of the Indonesian National Police (Polri) as a noble profession (officium nobile). Every member of the police force is expected to preserve their dignity and honor as individuals entrusted by society to maintain public order and security, to enforce the law in times of legal conflict, and ultimately, to offer protection and guidance to the community. This study aims to analyze the enforcement of the Police Professional Code of Ethics in response to cases of desertion by police officers that result in dishonorable discharge within the jurisdiction of the Riau Regional Police (Polda Riau). Specifically, the study examines the legal enforcement process, the barriers faced, and the efforts made to overcome those obstacles. This research employs a sociological legal approach. The findings reveal that enforcement of the Police Code of Ethics in desertion cases that end in dishonorable discharge is carried out firmly in accordance with Chief of Police Regulation Number 7 of 2022 on the Police Code of Ethics. Each proven case of severe desertion leads directly to an ethics tribunal, where—if found guilty—the officer is sanctioned with dishonorable discharge. The process begins with attendance verification, clarification, and the preparation of documents for the ethics hearing. This firm stance reflects the professionalism and institutional commitment of Polri. However, it also highlights a lack of preventive and developmental approaches, particularly in the early stages before violations occur. The main barriers in enforcing the code include: (1) systemic weaknesses in attendance reporting, where desertion cases are often detected too late due to unmonitored absenteeism; (2) organizational structural issues, where the guidance and mentoring functions remain reactive rather than proactive; and (3) organizational cultural tendencies to treat violations solely as grounds for punishment, without addressing underlying causes such as psychological stress, family problems, or work fatigue. Efforts to overcome these challenges include: (1) digitalizing the attendance and reporting systems to enable real-time monitoring; (2) strengthening moral and mental development, especially for personnel in remote or high-stress areas; (3) establishing internal preventive support systems, such as communication forums, counseling services, and informal coaching activities; (4) introducing tiered sanction policies, with dishonorable discharge reserved for repeated or severely intentional desertion; and (5) reforming organizational culture to foster more open, communicative, and supportive interactions between superiors and subordinates.